PENGARUH PENDAPATAN ASLI DAERAH DAN BELANJA MODAL TERHADAP INDEKS PEMBANGUNAN MANUSIA PADA PEMERINTAHAN DAERAH DI PULAU TIMOR PERIODE 2013-2018 - Made Denny Oktariyana; Christian Timotius Peilouw (JAKA - Jurnal Jurusan Akuntasi, 2022)
This study aims to determine the effect of Regional Original Income and Capital Expenditures on the Human Development Index in Regional Governments on the mainland of Timor Island. The Human Development Index shows the success rate of development in a region. This research covers 5 districts and 1 city on the island of Timor. The data collected is secondary data in the form of Human Development Index figures obtained from the official website of the Central Bureau of Statistics and Budget Realization Reports for District/City Governments on the mainland of Timor Island obtained from the Regional Finance Board of East Nusa Tenggara Province for the 2013-2018 period. The sample in this study amounted to 35 with the technique of paying using the saturated sample method. The data analysis technique used is multiple linear regression with the help of the SPSS program. The results of this study indicate that Regional Original Income has a positive and significant effect on the Human Development Index, while Capital Expenditure has no effect on the Human Development Index